Implementation of the Experimental Design Outcome in the Chemical Engineering Degree Program at Technical University of Madrid (GIQ-ETSII-UPM) - de la Fuente García-Soto, M. del Mar; Martínez-Urreaga, Joaquín; Narros Sierra, Adolfo (Journal of chemical education, 2022)
This paper presents an insight on the pedagogy and strategic design of the organization of the four experimental subjects of the Chemical Engineering Degree Curricula at the Universidad Politécnica de Madrid (GIQ-ETSII-UPM). Outcome-based learning is applied, focused on the student’s work, centering explicitly in Experimental Design outcomes. These skills are necessary not only for research, but also for innovation activities that will be fundamental for future engineers and chemists, and students should be encouraged to practice them during their time at university. The learnings are graduated following the requirements of the courses, and experimentations are realistic and easily approached as guided or free experimentation. Students must apply previous knowledge and acquire new ones, implement attitudes, work in teams, and make their own decisions. Among the students’ free comments collected in teacher surveys carried out on more than 400 students over 10 years, there are recurrent evaluations such as “We are able to put into practice what we have studied in other subjects”. These subjects are the ones students perceive as very important toward their future. Feedback is essential to improve their experimental proposals and make them viable to avoid student frustration. The number of teachers involved is between a minimum of 3 and a maximum of 7 for 30–40 students and 14 sessions in each subject. It is essential to note that the teacher’s engagement is indispensable for the performance of this framework.